Let's talk relationships : activities for exploring love, sex, friendship and family with young people - Rogers, Vanessa (Jessica Kingsley Publishers, 2011)
Let's Talk Relationships offers a multitude of creative ways to get young people aged 13-19 talking about positive relationships, helping them to stay safe, healthy and happy. Ideal for groups or one-to-one work, this resource features over 90 tried and tested activities.